Integrated multi-material portable 3D-printed platform for electrochemical detection of dopamine and glucose. Issue 20 (16th September 2022) - Domingo-Roca, Roger; Macdonald, Alexander R.; Hannah, Stuart; Corrigan, Damion K.
Abstract : Design and production of a one-step 3D-printed functional electrochemical biosensor for efficient detection of dopamine and glucose in low-volume samples (100 μL). Glucose detection via ruthenium-mediated amperometry provides results in 60 seconds. Abstract : 3D-printing has become a fundamental part of research in many areas of investigation since it provides rapid and personalized production of parts that meet very specific user needs. Biosensing is not an exception, and production of electrochemical sensors that can detect a variety of redox mediators and biologically relevant molecules has been widely reported. However, most 3D-printed electrochemical sensors detailed in the literature rely on big, individual, single-material electrodes that require large sample volumes to perform effectively. Our work exploits multi-material fused filament fabrication 3D-printing to produce a compact electrochemical sensor able to operate with only 100 μL of sample. We report cyclic voltammetry, differential pulse voltammetry, and chronoamperometry results to assess sensor performance and sensitivity. We investigated the influence of layer print orientation and layer thickness on the electrochemical performance of the sensor, and used the optimal parameters to produce the final device. The integrated 3D-printed platform successfully detects electrochemical activity for hexaammineruthenium(iii ) chloride and potassium ferricyanide (0.1 mM to 2 mM in 100 mM KCl), dopamine (50 μM to 1 mM in 1×PBS), and glucose via mediated amperometric glucose oxidase enzyme-based sensing (1 mM to 12 mM in 1×PBS), indicating good acceptance of biological modification. These results reveal the exciting potential of multi-material 3D-printing and how it can be used for the rapid development of efficient, small, integrated, personalized electrochemical biosensors.